Development and validation of two analytical methods for urea determination in compound feed, including pet food, and yeast using high-performance liquid chromatography coupled with fluorescence detection and tandem mass spectrometry. Issue 6 (3rd June 2021) - Krämer, Marco; Fry, Hildburg; Kappenstein, Oliver
ABSTRACT: Urea is authorised in the European Union (EU) as feed additive for ruminants. Because of its high molecular nitrogen content, it is a substance for potential protein adulteration in non-ruminant feed. The EU defines a spectro-colorimetric method as an official control method for the determination of urea in feed, whereas the Association of Official Analytical Chemists (AOAC) in the United States recommends an enzymatic method. Discrepancies between results obtained by these different approaches have been reported, especially at low concentrations. Therefore, we developed and validated two methods for urea determination in compound feed, including pet food, and yeast ( Saccharomyces cerevisiae ) over a wide concentration range using high-performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) and fluorescence detection (HPLC-FLD) and compared performance with a commercial enzyme kit. Limit of detection (LOD) and limit of quantification (LOQ) were found to be 3 and 8 mg kg −1 for LC-MS/MS and 2 and 7 mg kg −1 for HPLC-FLD, respectively. For both methods, the variation coefficients ranged between 1.4% and 7.2% in ruminant feed used as reference material as well as spiked samples of complete feed for chicken, pet food for dogs and cats, as well as yeast. Recovery rates for spiked samples ranged from 86% to 105%. For real samples of complete feed for poultry, wet and dry pet food for cats and dogs and yeast amounts of urea between < LOD and 200 mg kg −1 relative to a feedingstuff with a moisture content of 12% were found. In comparison with the enzyme kit, the newly developed methods proved to be less time-consuming in sample preparation and more stable regarding matrix effects.